Caring for more than teeth - Dr Delyse Lam; Dr Trupta Desai; Ms Cecilia Correy; Shane Brown; Mrs Natalia Uthurralt (Elsevier, 2023)
Aim or Purpose: To investigate dental clinician's perceptions regarding their role in identifying and understanding social and other health needs of vulnerable population seen in public dental services. Materials and Methods: An online anonymous cross-sectional survey was conducted over a period of 3 months between September and November 2022. The participants included all public dental clinicians working in Sydney Local Health District, Oral Health Service. The survey was designed to gauge the role of the dental clinician in identifying and understanding the social determinants of health that impact public dental patients. Likert-scaled questions were mostly utilised to determine how strongly participants held these personal beliefs and professional views regarding patients' social and other health needs. The survey also included an open-ended question to allow participants to discuss any other aspects not covered in the questionnaire. The study was approved by the RPAH Ethics Committee. The findings were summarised using descriptive statistics. Results: The overall response rate was 42% (n=40) and all clinicians strongly agreed/agreed that patient's social risk factors impacted their oral health and ability to attend dental appointments. Despite, 88% strongly agreed/agreed that addressing patients' non-dental needs fell within their professional responsibility, 70% strongly agreed/agreed that they were able to identify their patient's non-dental health and wellbeing needs. Only 30% strongly agreed/agreed that they had adequate training and resources and 32% were confident to refer their patients for non-dental health and wellbeing needs. Conclusions: Public dental clinicians identified the need for specific training to improve their knowledge and confidence to respond to their patients' social and other health needs.